Genomic analyses of two Alteromonas stellipolaris strains reveal traits with potential biotechnological applications - Torres, Marta; Hong, Kar Wai; Chong, Teik Min; Reina, José Carlos; Chan, Kok Gan; Dessaux, Yves; Llamas, Inmaculada (Nature Research, 2019)
The Alteromonas stellipolaris strains PQQ-42 and PQQ-44, previously isolated from a fish hatchery, have been selected on the basis of their strong quorum quenching (QQ) activity, as well as their ability to reduce Vibrio-induced mortality on the coral Oculina patagonica. In this study, the genome sequences of both strains were determined and analyzed in order to identify the mechanism responsible for QQ activity. Both PQQ-42 and PQQ-44 were found to degrade a wide range of N-acylhomoserine lactone (AHL) QS signals, possibly due to the presence of an aac gene which encodes an AHL amidohydrolase. In addition, the different colony morphologies exhibited by the strains could be related to the differences observed in genes encoding cell wall biosynthesis and exopolysaccharide (EPS) production. The PQQ-42 strain produces more EPS (0.36 g l−1) than the PQQ-44 strain (0.15 g l−1), whose chemical compositions also differ. Remarkably, PQQ-44 EPS contains large amounts of fucose, a sugar used in high-value biotechnological applications. Furthermore, the genome of strain PQQ-42 contained a large non-ribosomal peptide synthase (NRPS) cluster with a previously unknown genetic structure. The synthesis of enzymes and other bioactive compounds were also identified, indicating that PQQ-42 and PQQ-44 could have biotechnological applications. © 2019, The Author(s).